Intestinal parasites and lungworms in stray, shelter and privately owned cats of Switzerland. (April 2019) - Zottler, Eva-Maria; Bieri, Monika; Basso, Walter; Schnyder, Manuela
Abstract: Endoparasitic infections represent relevant causes of respiratory and gastrointestinal diseases in cats. The aim of the study was to investigate the occurrence of endoparasites in Swiss cats in order to evaluate the risk of onset of parasitic diseases and potential correlated zoonoses. Therefore 664 faecal samples from privately owned ( n  = 299), shelter ( n  = 197) and stray ( n  = 168) cats were investigated by sedimentation-flotation and 468 samples additionally by the Baermann technique. Overall, 77.4% ( n  = 130), 21.8% ( n  = 43) and 11.7% ( n  = 35) of stray, shelter and privately owned cats, respectively, were positive, with significant differences between the groups. Among infected cats, 58.7% ( n  = 122) harboured a single, 30.8% ( n  = 64) two and 10.6% ( n  = 22) more than two parasite species. Toxocara cati, with an infection rate of 18.5% ( n  = 123), was the most frequently detected parasite. The rates for other intestinal parasites were: Taenia sp. 11.1% ( n  = 74), Isospora sp. 8.1% ( n  = 54), Capillaria sp. 4.7% ( n  = 31), hookworms 1.1% (n = 7), Giardia duodenalis 0.8% (n = 5), Dipylidium caninum 0.6% ( n  = 4), Toxoplasma gondii 0.6% (n = 4), Hammondia hammondi 0.5% ( n  = 3), Sarcocystis sp. 0.2% ( n  = 1) and Diphyllobothrium latum 0.2% (n = 1). First-stage larvae of the lungworm Aelurostrongylus abstrusus were found in 2.3% ( n  = 15) of all samples. The morphological identification of Taenia sp., T. gondii, H. hammondi and A. abstrusus was confirmed by molecular techniques. Overall, cats younger than one year and intact animals were more frequently infected with parasites than older and neutered animals. The observed infection rates were comparable to those from other European studies, except for Taenia sp. showing a significantly higher occurrence. This implicates that there is a persistent risk of environmental contamination with parasitic stages especially by stray cats, and a risk of infection for cat owners with potential zoonotic pathogens, emphasizing the need for appropriate parasite control measures. Highlights: 31% of 664 Swiss cats were infected by endoparasites, stray cats more frequently than shelter and privately owned cats Helminths: Toxocara cati 18.5%, Taenia sp. 11.1%, Aelurostrongylus abstrusus 2.3% Protozoa: Isospora sp. 8.1%, Giardia sp. 0.8%, Toxoplasma gondii 0.6% Cats < one year and intact animals were more frequently infected with parasites Parasite control measures are needed to reduce environmental contamination by cats